The oasis of Khaybar Through Time: Historiography and preliminary results of the Khaybar Longue Durée Archaeological Project (2020-2024) - Charloux, Guillaume; Crassard, Rémy; AlMushawh, Munirah; Albukaai, Diaa; Chung-To, Guillaume; Depreux, Bruno; Guadagnini, Kévin; Hapiot, Laurence; McPhillips, Stephen; Régagnon, Emmanuelle; et al. (Proceedings of the Seminar for Arabian Studies, 2023)
The Khaybar oasis is a cultural landscape that has been shaped over thousands of years by human occupation and where communities continue to live to present day. It lies on the edge of a large lava field called Ḥarrāt Khaybar in Northwest Saudi Arabia. It combines unique geology, rich archaeology, and spectacular traditional heritage. It has been preserved for millennia, and human presence seems to go back from the earliest prehistoric times to the birth of Islam, and beyond. This article presents a primary general assessment of the archaeology for this major Arabian oasis. It aims to introduce the objectives and methods of our new survey and excavation project, the Khaybar Longue Durée Archaeological Project (2020-2024), supported by the Royal Commission for AlUla (RCU), the French Agency for AlUla Development (AFALULA), and the French Centre for Scientific Research (CNRS). It also highlights the preliminary results of field surveys carried out inside the RCU oasis core zone in Khaybar in November 2020 and June 2021. The project yielded important discoveries in its first seasons of activity, such as the presence of Palaeolithic and Neolithic occupations, the identification of specific patterns of local desert kites, the first analyses of protohistoric funerary structures, the discovery of a monumental pre-Islamic rampart that surrounded the oasis in the past, new pre-Islamic and Islamic sites, as well as a significant number of inscriptions and rock art from different periods and traditions.